Pengelolaan Program Diklat Berjenjang Tingkat Dasar Dalam Meningkatkan Kompetensi Pedagogik Pendidik Di PAUD Cempaka Cakung Barat Jakarta - Ayuningrum, Esti; Widodo, Widodo (J+PLUS UNESA, 2024)
Training management is a systematic and planned effort to optimize all training components in order to achieve program objectives effectively and efficiently. Education and training management is a series of processes that include training and part of educational activities. This research aims to describe the results of the problem formulation regarding the management of basic level education and training in improving the pedagogical competence of educators. This research method uses a descriptive qualitative method where data is obtained through in-depth interviews, participant observation and documentation studies. The data analysis technique in this research consists of data reduction, data presentation, and drawing conclusions or verification. The research results show that (1) management of basic level education and training programs has structured and well-organized stages, which include planning, organizing, implementing, monitoring and evaluating; (2) erly childhood educators' pedagogical competence includes several aspects which include, the ability to understand students, systematic learning planning, implementation of educational and logical learning, evaluation of learning outcomes, and development of students' potential.